Facing the Pressure: The Dynamics of Anxiety Among Final-Year Students Working on Their Theses - Rabbani, Deva Hasnah; Safitri, Ajeng; Fitriyana, Nur (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Anxiety among final-year students in thesis writing often becomes a major barrier to completing their studies, triggered by various internal and external factors such as academic pressure, family expectations, and technical issues. This study aims to analyze the dynamics of anxiety among students, focusing on the causes, symptoms, impacts, and solutions applied to manage this anxiety. Using a qualitative approach, the research collected data through in-depth interviews with four students who experienced anxiety during the thesis process. The findings show that student anxiety is caused by factors such as academic pressure, high family expectations, as well as physical and psychological disturbances such as sleep disorders, muscle tension, and feelings of restlessness. As a solution, students applied time management, sought social support, and engaged in physical activities to alleviate their anxiety. These findings have important implications for universities to provide more systematic psychological support to improve student well-being.Kecemasan pada mahasiswa tingkat akhir dalam pengerjaan skripsi sering menjadi hambatan besar dalam penyelesaian studi, dipicu oleh berbagai faktor internal dan eksternal seperti tekanan akademik, ekspektasi keluarga, dan masalah teknis. Penelitian ini bertujuan untuk menganalisis dinamika kecemasan mahasiswa, dengan fokus pada faktor penyebab, gejala, dampak, dan solusi yang diterapkan untuk mengatasi kecemasan tersebut. Menggunakan pendekatan kualitatif, penelitian ini mengumpulkan data melalui wawancara mendalam dengan empat mahasiswa yang mengalami kecemasan selama proses pengerjaan skripsi. Hasil penelitian menunjukkan bahwa kecemasan mahasiswa disebabkan oleh faktor-faktor seperti tekanan akademik dan ekspektasi yang tinggi dari keluarga, serta gangguan fisik dan psikologis seperti gangguan tidur, ketegangan otot, dan perasaan gelisah. Sebagai solusi, mahasiswa menerapkan manajemen waktu, mencari dukungan sosial, dan melakukan kegiatan fisik untuk meredakan kecemasan. Temuan ini memiliki implikasi penting bagi perguruan tinggi untuk menyediakan dukungan psikologis yang lebih sistematik guna meningkatkan kesejahteraan mahasiswa.